AN OVERVIEW ON DIABETES MELLITUS: MATHEMATICAL APPROACH (Journal of Pharmaceutical Negative Results, 2022)
Diabetes mellitus, sometimes known as diabetes, is a widespread disease in the current technological period. Blood glucose levels in this condition are out of the normal range of 80 to 170 mg/dl, which puts the human body at risk for long-lasting illness. Diabetes raises a person's mortality risk. Many reviews have been written about mathematical modelling for diabetes. Various models have been presented in recent years for a number of diabetes-related topics, including glucose and insulin dynamics, management and the prevention of complications, and the epidemiology of diabetes in general. On a regular basis, reviews on mathematical models used for particular areas of diabetes are published. This study offers an overview of several mathematical models that deal with various elements of diabetes.